Infectious myonecrosis virus and white spot syndrome virus co-infection in Pacific white shrimp (Litopenaeus vannamei) farmed in Brazil - Feijó, Rubens G. (2013)
Over the past few years, infectious myonecrosis virus (IMNV) and white spot syndrome virus (WSSV) have caused substantial economic losses to Brazilian shrimp farmers. Initially reported from different geographical locations within the country, these pathogens are becoming increasingly prevalent throughout Brazil. In the present study, 30 diseased shrimp collected from a farm in Northeastern Brazil were screened for viral infec- tion. The shrimp were submitted to histological analysis and quantitative real-time PCR (qPCR). New probes and primers were designed for the qPCR assays, and IMNV detection was based on a modified protocol. Clin- ical signs of both white spot syndrome and infectious myonecrosis were observed in histological preparations from four of the sampled shrimp. The presence of both IMNV and WSSV was confirmed by qPCR in twelve specimens. Viral co-infection has previously been reported in farmed shrimp. However, this is the first Bra- zilian report of co-infection with IMNV and WSSV in farmed Litopenaeus vannameI.